Cutis Laxa Syndrome: A Rare Genetic Disorder of Elastolysis - Rahman, Md Mizanur; Bhuiyan, AKM Tajuddin; Islam, Md Atiqul (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2018; 34(1) : 59-62